The Effectiveness of Online Learning on Psychology Education Courses of Children With Special Needs in Special Education Students - Hayatun Thaibah; Muhammad Arsyad (IJORER : International Journal of Recent Educational Research, 2023)
The role of educators is to develop teaching methods in the Psychology of Educational Children with Special Needs lectures so that students gain knowledge, learning experiences, and easy access through online discussion forums during the COVID-19 pandemic. This study aimed to determine the effectiveness of online learning on educational psychology courses for special education students. This research hypothesizes that the online teaching method using WhatsApp is effective for The Educational Psychology of Children with Special Needs course. The research method is a Quasi Experiment. The subjects of this study were students of special education study programs at the University of Lambung Mangkurat, Banjarmasin city. The data collection method used the test method, through pre-test and post-test. The data analysis technique is the t-test technique. The results of the research from pre-test and post-test data using a paired sample-t test showed that the activities of special education students in the educational psychology course for Children with Special Needs using online learning using WhatsApp turned out to be quite effective.